2010
DOI: 10.1111/j.1439-0531.2010.01691.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Activity and Morphology in Developing Porcine Oocytes and Pre‐implantation Non‐Cultured and Cultured Embryos

Abstract: Mitochondria are important determinants of developmental competence for oocytes and embryos owing to their central role in cellular metabolism, yet mitochondrial activity and morphometry during early porcine development have not been quantified. In this study, we examined the membrane potential Δψ(m) and the surface density Sv(in,m) of the inner mitochondrial membrane in pig oocytes and pre-implantation embryos using fluorescent probes and confocal microscopy. Mitochondria and their cristae were also examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 52 publications
1
20
0
1
Order By: Relevance
“…In most in vivo‐ and in vitro‐control matured oocytes, the mitochondria were distributed throughout the cytoplasm, although more abundant in the periphery, with strong staining in the first polar body (85% and 90%, respectively). This finding is consistent with previous reports from several species, including porcine (Sun et al, 2001; Katayama et al, 2006; Romek et al, 2011), bovine (Hyttel et al, 1986; Stojkovic et al, 2001), mouse (Tokura et al, 1993), and hamster (Barnett et al, 1996). Exposing oocytes to H342/UV, however, disrupted this pattern and the number of oocytes with this mitochondrial pattern tended to decrease ( P = 0.15) compared to the non‐exposed, matured oocytes.…”
Section: Discussionsupporting
confidence: 91%
“…In most in vivo‐ and in vitro‐control matured oocytes, the mitochondria were distributed throughout the cytoplasm, although more abundant in the periphery, with strong staining in the first polar body (85% and 90%, respectively). This finding is consistent with previous reports from several species, including porcine (Sun et al, 2001; Katayama et al, 2006; Romek et al, 2011), bovine (Hyttel et al, 1986; Stojkovic et al, 2001), mouse (Tokura et al, 1993), and hamster (Barnett et al, 1996). Exposing oocytes to H342/UV, however, disrupted this pattern and the number of oocytes with this mitochondrial pattern tended to decrease ( P = 0.15) compared to the non‐exposed, matured oocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Although the increase of mitochondrial activity during bovine embryo development was previously described (Tarazona et al 2006), it is believed that mitochondria of oocyte origin are responsible for energy supply during development, since there is no synthesis of new organelles until the blastocyst stage (Van Blerkom 2011). Although there is a consensus regarding the increase in mitochondrial activity during in vitro maturation (IVM) in different species (Tarazona et al 2006;Romek et al 2011), lipid behaviour and the interaction with mitochondria, at this stage, remain poorly understood. Recently, studies have shown an increase of lipid, particularly TG, in the oocyte during bovine IVM, with or without FBS in the maturation media (Ferreira et al 2008;Aardema et al 2011;González-Serrano et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is also at this stage of development that the mitochondrial contingent mature and adopt the traditional oblong shape (Crocco et al, 2011) which is followed by a significant raise in mitochondrial activity (Tarazona et al, 2006) as well as an increase in mtDNA copy numbers (Chiaratti et al, 2010;Wai et al, 2010). This confirms that prior to genome activation, mitochondrial functions are limited (Tarazona et al, 2006;Romek et al, 2010) and that conversely, mitochondrial potential common to somatic cells is established between 8-16 cells and the morula stage in bovine embryos in bovine.…”
Section: Reviewmentioning
confidence: 61%
“…It is only following genome activation, which occurs at the 8-cell stage in bovine (Memili and First, 1998) that blastomeres begin to die by apoptosis (Tarazona et al, 2006). It is also at this time, between 72 and 168 hours post fertilization, that mitochondrial activity shows a slight increase in activity as observed by oxygen consumption and ATP production at the morula stage (Tarazona et al, 2006;Romek et al, 2010). It is also at this stage of development that the mitochondrial contingent mature and adopt the traditional oblong shape (Crocco et al, 2011) which is followed by a significant raise in mitochondrial activity (Tarazona et al, 2006) as well as an increase in mtDNA copy numbers (Chiaratti et al, 2010;Wai et al, 2010).…”
Section: Reviewmentioning
confidence: 99%